PERSEPSI AUDITOR TENTANG MOTIVASI AUDITEE MELAKUKAN AKUNTANSI KREATIF (CREATIVE ACCOUNTING) - Elisabeth Juliaz Solicha; Deliza Henny (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
This research objective is to know how the perception of senior and junior auditors, whether there are differences between them, regarding of creative accounting practices conducted by the auditee. This research sample are consist of auditor at public accounting firms in the area of Tangerang and Jakarta with 86 respondents. Data were obtained from questionnaires which distributed to the research place. Tests on this research using validity test, reliability test and hypotheses test through independent sample t test. The results of this research stated that the whole auditors (senior or junior) agree with the creative accounting practice done by auditee and there were no difference in perception between senior and junior auditors on the creative accounting practice that assessed by three components of assessment, that are business ethics, quality of financial statements and manager motivation